THE EFFECT OF THINK PAIR ON STUDENTS’S WRITING SKILL THROUGH PADLET FOR TENTH GRADE AT SMA MUHAMMADIYAH IX BRONDONG - Muslimah, Mujahidatul; Anwar, Khoirul; Asmara, Candra Hadi (Journal of English Teaching, Literature, and Applied Linguistics, 2020)
Good writing is important aspect in teaching writing subject. But, the researcher find on the students some problems that they faced in their writing which are in generating the ideas, orginizing and vocabulary. Besides, the teacher also has problems in applying the appropriate strategy and media in teaching writing. Based on the previous studies, Think Pair Share strategy gave the positive effect for the students. This study was to examine the significant effect of Think Pair Share on Student’s Writing Skill through Padlet for Xth Grade at SMA Muhammadiyah 9 Brondong. And the researcher uses quasi Experimental design. The researcher choose Tenth grade at SMA Muhammadiyah 9 Brondong which totally consisted of 56 students. The researcher used cluster sampling because the school has been detemined the classification of the students. It was included 28 students of X IPA 1 as the Experimental Group and 28 students of X IPA 2 as the Control Group. The data was gathered by utilizing tests; pre-test and post-test about composing illustrative content. In the wake of getting the information, the specialist broke down the information utilizing SPSS 16.0 and utilized Independent Sample T-test. The examination finding indicated that there was a noteworthy contrast between test bunch that were educated by utilizing Think Pair Share through Padlet and control bunch that were instructed by utilizing Think Pair Share through Pictures.. It was Therefore, the researcher suggest to the English teacher for implementing of Think Pair Share strategy through Padlet as an altenative strategy in English teaching learning process and hopes to use Think Pair Share strategy through Padlet in other skills and levels to make different with the previous study.proven by the result of sig.(2tailed) is .000. The sig. (2tailed) is lower than 0.05 (0.00 < 0.05) so, null hypothesis (H0) can be rejected. The researcher concluded that Think Pair Share Strategy gave positive effect on student’s writing skill. The students were motivated and independent in learning writing especially in eneratig the ideas, organizing the ideas, and vocabulary. This research contributes by forming new think pair share steps which are associated with the use of technology that can help students much better in discussing in a learning that is the padlet.